De la défiance à la réconciliation : itinéraires des constructions urbaines et rivulaires des villes du Sillon lorrain (Nancy, Metz, Thionville) - Denis Mathis; Anne Hecker; Jean-Pierre Husson; Kamila Bensaadi (Projets de Paysage)
This study observes and analyses geohistorical relationships within cities and their rivers and urban hydromorphology at the scale of the Sillon Lorrain urban cluster. These relationships, which were often conditioned by mistrust within an urban development context, are now evolving towards a more balanced approach to planning based on the logic of river management and are thus towards a more harmonious relationship. This new approach involves a transition in landscape planning involving the pairing of urban centres and their rivers. Riversides are enhanced, facilitating transpositions of urban rehabilitation or regeneration operations which account for the heritages and unique qualities of the cities of Nancy, Metz and Thionville. This new approach is based on a “narrative” and on “memory” which are put at the service of reconciliation and the construction or consolidation of urban waterfronts.